Hubungan Penyakit Komorbid dengan Status Mortalitas Pasien COVID-19 - Delvira Azzahra; Suganda Tanuwidjaja; Rika Nilapsari (UNISBA Press, 2024)
Abstract. Coronavirus disease-19 (COVID-19) is a disease caused by infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). From January to May 20, 2020, a total of 4,806,299 people have been infected and caused 318,599 deaths worldwide. One of the risk factors for COVID-19 is comorbid diseases. Individuals who have comorbidities can make COVID-19 more severe and can increase mortality. The purpose of this study was to determine the relationship between comorbid diseases and mortality status of COVID-19 patients. This study was observational analytic using a cross-sectional study. The study was conducted from February – August 2023. Research materials were taken from medical records, obtained 184 secondary data that met the inclusion criteria. Data were collected using total sampling and analyzed using the Fisher method. The results showed that the number of patients who had comorbidities was 77.7% dominated by lung disease (48.4%). There is a relationship between comorbid diseases and mortality status with a p value of 0.000. This result can occur because it is influenced by various worsening mechanisms that occur in individuals with comorbid diseases. Abstrak. Coronavirus disease-19 (COVID-19) adalah suatu penyakit yang disebabkan oleh infeksi severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Terhitung sejak Januari sampai 20 Mei 2020, sejumlah 4.806.299 orang telah terinfeksi dan menyebabkan 318.599 kematian di seluruh dunia. Salah satu faktor risiko COVID-19 penyakit komorbid. Individu yang mempunyai penyakit penyerta dapat menyebabkan COVID-19 yang dideritanya menjadi lebih berat dan dapat meningkatkan angka mortalitas. Tujuan penelitian ini adalah untuk mengetahui hubungan penyakit komorbid dengan status mortalitas pasien COVID-19. Penelitian ini adalah observasional analitik menggunakan cross-sectional study. Penelitian dilakukan dari Februari – Agustus 2023. Bahan penelitian diambil dari rekam medis, didapatkan 184 data sekunder yang memenuhi kriteria inklusi. Pengambilan data menggunakan total sampling dan dianalisis menggunakan metode Fisher. Hasil penelitian menunjukkan jumlah pasien yang memiliki komorbid adalah 77.7% yang didominasi oleh penyakit paru (48,4%). Terdapat hubungan antara penyakit komorbid dengan status mortalitas dengan p value 0,000. Hasil ini bisa terjadi karena dipengaruhi oleh adanya berbagai mekanisme perburukan yang terjadi pada individu dengan penyakit komorbid.